The process of convergence in common law of the perm and the samoyed peoples (Journal of actual problems of jurisprudence, 2021)
Significant peculiarities of the convergence process among the Samoyed and Finno-Ugric peoples of the Perm subgroup are investigated in the current paper. The author aims at the investigation of convergence process of the common legal institutions and regulations of the peoples under consideration among themselves, with neighboring peoples without excluding mutual reception between the positive law norms of the Russian State and common legal norms. Various common legal institutions used in the past among these peoples are considered in the given paper. Special attention is paid to a convergence process investigation of common legal institutions and norms among the Perm and the Samoyed peoples. The author emphasizes existence of varied external contacts among the peoples under consideration, influence on them by neighbouring peoples and possible mutual reception of various legal institutions. Making use of empiric material, the author explains specific features of asymmetry formation between dominant and peripheral legal culture. The author comes to a conclusion that approximation of legal institutions practiced in common law of the Perm and the Samoyed peoples constantly occurred both between them and with common legal elements of the peoples lived in the closest proximity with them. Apart from that, on the basis of the examples revealing process of influence of peasant populace legal views on positive law formation, the author distinguishes peculiarities of the convergence process between positive laws norms, dominated in the state and common legal norms among the Perm and the Samoyed peoples.Keywords: common law, the Perm peoples, the Samoyed peoples, positive law, custom, convergence.